(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the basis for the emergence of property rights, the legal regulation of property rights based on the norms existing in our legislation, the legal basis for the emergence of property rights, and the right of ownership of property are described.